From ‘‘pasokification’’ to ‘‘de-pasokification’’? PASOK’s deviation from its political tradition (2012-2020) - Eleftheriou, Costas; Tassis, Chrysanthos D. (The Greek Review of Social Research, 2022)
The present article analyzes PASOK’s path from 2012 to 2020 and its adaptation to its '‘post-hegemonic’' phase. Its hegemonic position in the Greek party system stemmed from a political tradition corresponding to three dimensions (organizational, ideological, and strategic). Since 2012, PASOK opted for a trajectory of adaptation to the new political environment that was created through its electoral demise.This process took the form of a triple deviation from this tradition. This shift is explained through three independent variables: the variable of the bailout programmes and the terms of their implementation; the variable of the party’s position in the post-2012 party competition; the variable of the cartelization of the party.